International Counseling Seminar 2016 (ICS2016) Plenary Speaker on Resilient Therapy as an Expansion of Counselling Services in Working with the Vulnerable Clients - Amalia, Madihie (2016)
Title: Resilient Therapy as an Expansion of Counselling Services in Working with the Vulnerable Clients